Implementation Of Epistemology In Arabic Language Learning: As A Theoretical Study - Prayoga Saputra; Robi’atul Laili Maulidiyah; Habibullah Muhammad; Muhammad Fadli (Yayasan Adra Karima Hubbi, 2023)
Background. This article delves into the realm of epistemology, a crucial branch of the philosophy of science that explores the nature of knowledge and its reflection on human reality. Method. The research methodology involves library research and descriptive research, with data collected from various reading materials, contributing to a comprehensive exploration of epistemology and its role in language education. Purpose. The research aims to 1) comprehend the concept of educational epistemology and 2) ascertain the role of epistemology in Arabic language learning. By achieving these objectives, the study seeks to provide insights into the application of philosophical knowledge in Arabic language education, specifically addressing the four language skills: listening, writing, speaking, and reading. Results. The discussion reveals three distinct epistemologies in Arabic language learning: Bayani emphasizes textual authority, Irfani relies on experiential knowledge through spiritual exercises, and Burhani relies solely on reason and logical evidence. These epistemologies shape the approach to understanding and acquiring knowledge, offering diverse perspectives within the context of Arabic language education.Top of Form. Conclusion. In conclusion, this article provides valuable insights into the essence of epistemology, its diverse applications in Arabic language learning, and the philosophical underpinnings of language education.